The Relationship Between the European Convention on Human Rights and Domestic Law: a Case Study - Kamil A. Strzępek (Constitutional Review, 2020)
The article is pertaining to the relationship between the European Convention on Human Rights and the Polish national law. Upon the introduction of the system of economic, social and cultural rights contained in the Constitution of the Republic of Poland of 1997, the article considers what rules determine the relationship between the application of the law by Polish courts and the European Court of Human Rights in Strasbourg. The paper concludes by showing how Polish courts and the European Court of Human Rights in Strasbourg refer to the right of property. It’s one of the fundamental human rights, when they examine a case. It occurs that clauses, which limit this right, are sometimes understood in a different way by Polish courts and the European Court of Human Rights. Regarding the above, the case of Waldemar Nowakowski v. Poland of the European Court of Human Rights in Strasbourg is discussed. Furthermore, the article presents how the Polish Government executes the judgment of the European Court of Human Rights in Strasbourg delivered in the above-mentioned case.